IMRPOVING STUDENTS’ MOTIVATION IN LEARNING ENGLISH USING DIGITAL PLATFORM : A LESSON STUDY IN SMK MUHAMMADIYAH BUMIAYU - Yanri Isfahani (Journal of Lesson Study in Teacher Education, 2022)
The success of learning activity is influenced by students’ motivation, teacher should be creative in order to enhance students’ enthusiasm, this may be accomplished by using digital platform such as google classroom, padlet, mentimeter, quizizz and classtools.net. Lesson study can be used to determine whether or not the usage of the digital platform is successful, that is implemented in a collaborative and sustainable way. This lesson study is implemented using a Project-based Learning (PjBL), an inquiry approach and students worksheet. This study used a qualitative approach with the descriptive analysis method. There are three stages of lesson study activities; plan, do, and see. The subject of the study was students of XI AKL SMK Muhammadiyah Bumiayu in academic year 2021/2022. The implementation of digital platform in teaching and learning activity was thoroughly well-conducted. through digital platform the students’ motivation is increasing, This can be seen from student enthusiasm, students’ collaboration, student involvement, and student interest in learning new applications.